Representation of Moral Values in the Film CODA: A Roland Barthes Semiotic Analysis - Adli Farhan Dafana; Fitri Yanti; Septy Anggrainy (Jurnal Ilmiah Syi'ar, 2026)
Representations of disability in film have long been dominated by passive and stereotypical portrayals, creating a need for deeper analysis of cinematic works that offer a different perspective. This study aims to understand how moral values are represented in the film CODA (2021) through Roland Barthes’ semiotic analysis. The approach used is qualitative descriptive, with analytical focus on scenes, dialogue, visual expressions, sign language, and audiovisual symbols collected purposively through close viewing technique. Research findings demonstrate that CODA constructs moral messages non-dogmatically through complex sign systems. Based on analysis of denotation, connotation, and mythic meanings, three primary moral values were identified. First, the value of sacrifice, represented through Ruby's daily routines, connoting forced maturity. Second, affection and empathy conveyed intimately through Frank's gesture of feeling Ruby's vocal vibrations while singing. Third, independence and responsibility reflected in Leo's character. Mythologically, the film successfully deconstructs various societal biases, including the Hearing Savior Complex myth. This research affirms that film can be an effective medium for reflecting ethical realities and educating social sensitivity toward the disabled community.